The acceptance of non-muslim consumers of halal products: a study case in Urban Transformation Centre (UTC) Johor Bahru / Nurul Sakinah Rahamat - Rahamat, Nurul Sakinah (2014)
The aims and purpose of this study is to determine the factor that likely influences non-Muslims' understanding of Halal principles in an Urban Transformation Centre (UTC) Johor Galleria at Kota Raya Johor Baharu. The primary focus on this research is non-Muslims' consumers. The researcher want identify the understanding of Halal principles among non-Muslims consumers. An addition, the researcher wants to determine factors. Those influences non-Muslim consumers of understanding halal principles and also consume the halal food or products. The advantage of consume halal product, and so on. In Islam halal means something which has been sanctioned by Islamic law. This product will be handling with high level of hygiene and safety. This research will involve 100 respondents in area UTC Galleria at Kota Raya. Based on this research the researcher can get information and knowledge about the non-Muslim understanding halal principles.